The Yankee way : playing, coaching, and my life in baseball - Randolph, Willie, 1954- (Itbooks, 2014)
An all-star baseball player, former Yankees co-captain, and former New York Mets manager describes his Brooklyn childhood, the family and friends who influenced his career, and his hard-won efforts to become a big-league coach.